Histopathological Changes in Placenta in Cases of Intrauterine Growth Restriction - Ghosh, Soma; Bhuniya, Shantanu; Biswas, Dilip Kumar (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Intrauterine growth retardation (IUGR) creates a significant worldwide public health burden being leading cause of perinatal mortality and morbidity. Objective: To determine correlation between placental pathology and IUGR, to assess pattern of placental histopathological changes in IUGR compared to uncomplicated pregnancy and to determine significant early neonatal outcome of IUGR baby in specific placental changes. Methods: A cross-sectional observational, descriptive study done in a study population of 100 placentae including 50 from uncomplicated pregnancy and 50 from IUGR cases. The histopathological, morphological changes of placentae in IUGR observed and compared with placentae of uncomplicated delivery for a period of eighteen months. All IUGR cases with time of delivery between 28 weeks and 40 weeks of gestation were included excluding multiple pregnancy and IUFD. Results: The mean gestational age in pre-term labor (PTL)was 30.4 weeks compared to 37.2 weeks in term population. Placental weight and diameter were reduced in PTL with decreased intervillous space, syncytial knot, terminal villous vascularity and stem villous fibrosis. Increased deposition of placental intervillous, perivillous fibrin; number of Hofbauer cells and fetal obstructive vascular lesions in PTL associated with different perinatal outcomes and mortality. Fetal Inflammatory Response was much higher in males. Increased stage, grade of infectious and ischemic changes of placentae were associated with more adverse outcomes. Conclusion: Adverse perinatal outcomes were more prevalent in preterm babies whose placentae showed infectious and ischaemic changes. An assessment of placental pathology is thus useful for resolving issues arising from pregnancy complications. International Journal of Human and Health Sciences Vol. 07 No. 03 Jul’23 Page: 252-261